KEADILAN, NEGARA DAN PEMBANGUNAN EKONOMI: PERSPEKTIF EKONOMI ISLAM - Malahayatie Malahayatie (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
This article aims to describe the theory of Islamic justice in a country in order to realize economic development evenly. The Islamic economic system is based on the principle of justice, this covers all basic aspects of the economy such as production, distribution, consensus and exchange. Justice is the most important pillar in the Islamic economy. In Islam the State has an important role in upholding this justice, so that the State must have policies or strategic steps for the realization of a just and prosperous economic development. Regarding justice, Ibn Khaldun has emphasized that justice is the backbone and principle of the strength of an economy. If justice cannot be implemented, then a country will be destroyed and destroyed. The state has a big responsibility in realizing just economic development. This requires that the community has the same opportunity to obtain a decent life, even though each society is distinguished by the level of potential, skill and intellectuals, as well as the economic life it has. In the Islamic economy justice is meant that the country together with its community is able to integrate synergistically to regulating the whole aspect of life into a whole set of entities. The justice to be achieved in this article also expects the nature and character of the community as the core of a country in order to have commendable traits in using all natural resources as capital for production, consumption and distribution. Keywords: Justice, State, Economic Development, Islamic Economy